2017
DOI: 10.3390/ma10030268
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Stable α + β Microstructures during Selective Laser Melting of Ti-6Al-4V Using Intensified Intrinsic Heat Treatments

Abstract: Selective laser melting is a promising powder-bed-based additive manufacturing technique for titanium alloys: near net-shaped metallic components can be produced with high resource-efficiency and cost savings. For the most commercialized titanium alloy, namely Ti-6Al-4V, the complicated thermal profile of selective laser melting manufacturing (sharp cycles of steep heating and cooling rates) usually hinders manufacturing of components in a one-step process owing to the formation of brittle martensitic microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 38 publications
2
95
0
Order By: Relevance
“…5 Recent developments have shown that SLM Ti6Al-4V in the as-built state can achieve a fully lamellar a + b microstructure via in situ martensite decomposition by manipulating SLM variables, including the focal off-set distance, energy density, inter-layer time and hatch spacing (the layer thickness was fixed at 60 lm). [7][8][9][10] In addition, tunable microstructural length scales and superior mechanical properties were achieved in SLM Ti-6Al-4V in the as-built state. These developments have made SLM of Ti-6Al-4V essentially similar to selective electron beam melting (SEBM) in terms of both the as-built microstructures and tensile properties.…”
Section: Introductionmentioning
confidence: 98%
“…5 Recent developments have shown that SLM Ti6Al-4V in the as-built state can achieve a fully lamellar a + b microstructure via in situ martensite decomposition by manipulating SLM variables, including the focal off-set distance, energy density, inter-layer time and hatch spacing (the layer thickness was fixed at 60 lm). [7][8][9][10] In addition, tunable microstructural length scales and superior mechanical properties were achieved in SLM Ti-6Al-4V in the as-built state. These developments have made SLM of Ti-6Al-4V essentially similar to selective electron beam melting (SEBM) in terms of both the as-built microstructures and tensile properties.…”
Section: Introductionmentioning
confidence: 98%
“…Depending on the support structure, layer thickness and part dimension, a varying α lath width can be achieved. In parallel to this work, Barriobero-Vila et al [21] proposed a laser scanning strategy which took advantage of the benefits offered by a longer IHT exposure time, so as to ensure α martensite decomposition into α + β by using porosity-optimised processing parameters previously developed by Kasperovich et al [22] and a tight hatch distance. Both studies demonstrate the evolving achievements in microstructure design control methods and the importance of localised cyclic reheating as one of the means to achieve tailored microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…2 Imaging beyond the depth-of-focus limit Present-day x-ray nanotomography is usually done within the depth of focus limit of Eq. 1 (18)(19)(20)(21)(22)(23)(24)(25)(26), such as with 1 µm resolution at 25 keV (giving λ = 0.050 nm and DOF=110 mm), or 20 nm resolution at 6.2 keV (giving λ = 0.20 nm and DOF=11 µm). In these cases, one can obtain an image that represents a pure projection through the specimen at each rotation angle by using standard phase retrieval methods based on the inversion of the Transport-of-Intensity equation (27); one can then use standard tomographic reconstruction algorithms such as filtered backprojection.…”
Section: Introductionmentioning
confidence: 99%